Principle of pro-poor tourism: Analysis of the positive and negative aspects - Škrbić Iva; Tomka Dragica; Milošević Srđan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2014)
Reducing poverty is one of the primary activities that must be implemented by developed countries and developing countries alike. Seeing as tourism has a major impact on the global and local economy through the implementation of the objectives of poverty reduction, the pro-poor tourism strategy must be included in the agenda of tourism development. The aim of the pro-poor strategy is to increase the economic and socio-cultural benefits for the local population. The theoretical frame for the creation of these strategies is almost inexistent, but a number of small initiatives is what indicates the further course of activities. Criticisms of the strategy of pro-poor tourism and problems occurring in practice should not be ignored, because the identification of these problems is the first step toward solving them and improving the existing strategies. Therefore, this paper aims to point out the advantages and disadvantages of applying the principle of pro-poor tourism. The subject of the paper is the identification of the key determinants of pro-poor tourism strategies and the requirements for the investors, tourists and local people to reap the benefits of pro-poor tourism.